2013
DOI: 10.1161/circulationaha.113.002624
|View full text |Cite
|
Sign up to set email alerts
|

Function and Distribution of Apolipoprotein A1 in the Artery Wall Are Markedly Distinct From Those in Plasma

Abstract: Background Prior studies show apolipoprotein A1 (apoA1) recovered from human atherosclerotic lesions is highly oxidized. Ex vivo oxidation of apoA1 or high density lipoprotein (HDL) cross-links apoA1 and impairs lipid binding, cholesterol efflux and lecithin cholesterol acyltransferase (LCAT) activities of the lipoprotein. Remarkably, no studies to date directly quantify either the function or HDL particle distribution of apoA1 recovered from the human artery wall. Methods and Results A monoclonal antibody (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 48 publications
3
100
0
2
Order By: Relevance
“…Recent studies reveal that apoA-I within human atherosclerotic plaque is 100-fold enriched compared with normal artery wall, predominantly lipid-poor, not associated with HDL, extensively oxidatively cross-linked, and functionally impaired with respect to both cholesterol efflux and LCAT activities (58). The present studies extend these observations by looking at a specific oxidized form of apoA-I that is abundant within the atherosclerotic plaque-laden artery wall.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Recent studies reveal that apoA-I within human atherosclerotic plaque is 100-fold enriched compared with normal artery wall, predominantly lipid-poor, not associated with HDL, extensively oxidatively cross-linked, and functionally impaired with respect to both cholesterol efflux and LCAT activities (58). The present studies extend these observations by looking at a specific oxidized form of apoA-I that is abundant within the atherosclerotic plaque-laden artery wall.…”
Section: Discussionsupporting
confidence: 67%
“…These results further underscore that what is occurring in the artery wall is quite distinct from what is happening in the plasma compartment. Consistent with this notion, recent studies using a monoclonal antibody specifically developed to recognize all forms of apoA-I equally well (lipidated and non-lipidated forms as either native or various oxidized forms alike) have shown that the function and distribution of apoA-I in the artery wall are markedly distinct from those in plasma (58).…”
Section: Discussionmentioning
confidence: 78%
“…Although our group confi rmed this result for prevalent CAD, we found a paradoxical result in that higher apoB-depleted serum cholesterol acceptor activity was associated with higher incident CAD in a longitudinal study Previously, Wu et al ( 49 ) demonstrated that MPO oxidation of reconstituted HDL (rHDL) impaired its ability to activate LCAT. Recently, DiDonato et al ( 50,51 ), made recombinant human apoA1 with the specifi c substitution of Tyr166 by nitro-tyrosine, incorporated by the use of an orthogonal nitro-tyrosine tRNA synthase. rHDL made with nitro-Tyr166 apoA1 was markedly impaired in its ability to activate LCAT compared with wild-type apoA1 ( 50,51 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, since the macrophages accumulate LDL-derived cholesterol, an imbalance between cholesterol influx and cholesterol efflux exists in the atherosclerosis-prone arterial intima. One reason for the relative inability of HDLs to effectively remove cholesterol from the intimal macrophages is their functional modification including proteolysis, oxidation, and lipolysis to various extents (Lee-Rueckert and Kovanen 2011;DiDonato et al 2013). …”
Section: Formation Of a Fatty Streakmentioning
confidence: 99%
“…Although not formally tested, it is also possible that, in order to reach the circulation again, HDL particles undergo transcytosis through the luminal endothelial cell barrier or transfer cholesterol to endothelial cells for delivery to circulating HDLs. The importance of a well-regulated homeostasis between entry and exit of HDL particles into and from the arterial wall, respectively, is indicated by the enrichment of modified and dysfunctional HDLs and apoA-I in atherosclerotic lesions (DiDonato et al 2013Huang et al 2014). …”
Section: Exit From the Arterial Wallmentioning
confidence: 99%